2014
DOI: 10.1002/anie.201402299
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyano‐Substituted Diaryltetracenes from Tetraaryl[3]cumulenes

Abstract: A versatile, two-step synthesis of highly substituted, cyano-functionalized diaryltetracenes has been developed, starting from easily accessible tetraaryl[3]cumulenes. This unprecedented transformation is initiated by [2+2] cycloaddition of tetracyanoethylene (TCNE) to the proacetylenic central double bond of the cumulenes to give an intermediate zwitterion, which after an electrocyclization cascade and dehydrogenation yields 5,5,11,11-tetracyano-5,11-dihydrotetracenes in a one-pot procedure. A subsequent copp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 51 publications
1
38
0
2
Order By: Relevance
“…All experimental methods, synthesis, and characterization are provided in the Supporting Information (Sections S1, S2 and S10). The Supporting Information contains the synthesis and full characterization of all new compounds, as well as copies of their 1 Ha nd 13 CNMR spectra, X-ray crystallography details and CIF files for compounds 12 and 16,c yclic voltammetry (CV), rotating disk voltammetry (RDV) and UV/Vis spectroelectrochemical data and spectral traces, quantum chemical calculations (DFT) on the conjugates and control compounds, UV/Vis spectra of the conjugates and control compounds, detailed report on the transient absorption spectroscopic measurements, and Marcus curves. CCDC 1051625 (12)a nd 1431981 (16)c ontain the supplementary crystallographic data.…”
Section: Methodsmentioning
confidence: 99%
“…All experimental methods, synthesis, and characterization are provided in the Supporting Information (Sections S1, S2 and S10). The Supporting Information contains the synthesis and full characterization of all new compounds, as well as copies of their 1 Ha nd 13 CNMR spectra, X-ray crystallography details and CIF files for compounds 12 and 16,c yclic voltammetry (CV), rotating disk voltammetry (RDV) and UV/Vis spectroelectrochemical data and spectral traces, quantum chemical calculations (DFT) on the conjugates and control compounds, UV/Vis spectra of the conjugates and control compounds, detailed report on the transient absorption spectroscopic measurements, and Marcus curves. CCDC 1051625 (12)a nd 1431981 (16)c ontain the supplementary crystallographic data.…”
Section: Methodsmentioning
confidence: 99%
“…Zwitterions 14 a-c give two reversible one-electron reduction steps and an irreversible two-electron oxidation step associated on the reverse scan to as mall amplitude peak at + 0. [8], and torsional angles [8]: 14 a C4AÀN4A 1.342(2), C4BÀ N4B 1.340(2), C3ÀC4 1.395(3), C3ÀC3D1.401(3);C 4-C3-C3D 126.0(2), C1-C2-C3-C4 À120.2(2); 15 b:C 1AÀN1A 1.440(1), C1BÀN1B 1.450(1), C3ÀC4 1.408(2), C3ÀC3D1.405(2);C4-C3-C3D 121.1(1), C1-C2-C3-C4 À35.9 (1). The quinoid character dro ft he anilinorings is calculated from the bond lengths in aniline moieties using the following formula: dr = {[(a + b)/2Àc] + [(a' + b')/ 2Àc']}/2 (in benzene, dr = 0; in fully quinoid rings, dr = 0.10-0.12 ).…”
Section: Proacetylenic Reactivity Of Push-pull [3]cumulenesand Propermentioning
confidence: 99%
“…More recently,w ep roposed the intermediacy of such zwitterions in the reaction of symmetrically substituted tetraaryl [3]cumulenes with TCNE at higher temperature (90-140 8C) in dipolar-aprotic solvents, leadingultimately to 5,11-dihydrotetracenes. [8,17] We coined the term" proacetylenic" to describe the acetylene-types tructure and reactivity of the central C=Cb ond in [3]cumulenes, [14] in analogy to the concept of proaromaticity of quinoidc hromophores. [18] According to Chauvin et al,b ut-3en-1-yne is significantly more "aromatic" than buta-1,2,3triene.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Shorter cumulenes, such as [3]cumulenes,w ere first reported by Brand in the early 1920s. [5,6] More recently,Diederich and co-workers have looked at the synthesis and reactivity of these systems [7,8] and an umber of push-pull/donor-acceptor [3]cumulenes. [9,10] Ueta et al have also reported the [2+ +2] cycloaddition of a[3]cumulene with tetracyanoethene.…”
mentioning
confidence: 99%